2016
DOI: 10.1016/j.susc.2015.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting formic acid decomposition on metallic powder catalysts: Exploding the HCOOH decomposition volcano curve

Abstract: This study revisits the classic volcano curve for HCOOH decomposition by metal catalysts by taking a modern catalysis approach. The metal catalysts (Au, Ag, Cu, Pt, Pd, Ni, Rh, Co and Fe) were prepared by H 2 reduction of the corresponding metal oxides. The number of surface active sites (Ns) was determined by formic acid chemisorption. In situ IR indicated that both monodentate and bidentate/bridged surface HCOO* were present on the metals. Heats of adsorption (ΔH ads) for surface HCOO* values on metals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 31 publications
(29 reference statements)
5
46
0
Order By: Relevance
“…The observation of formate at this temperature is consistent with this reaction on other cobalt surfaces and other transition metals 33,69 and with the low barrier in the reaction scheme. Formation of the carboxyl species should be expected at the same time as the formate, since the two paths have similar barriers, however the carboxyl species was not observed experimentally either because its C 1s signature could not be resolved (Table S1 lists the calculated peak positions for the C 1s photoelectron for all the fragments) or because it decomposes shortly after being produced via CO formation.…”
Section: Low Temperaturesupporting
confidence: 88%
“…The observation of formate at this temperature is consistent with this reaction on other cobalt surfaces and other transition metals 33,69 and with the low barrier in the reaction scheme. Formation of the carboxyl species should be expected at the same time as the formate, since the two paths have similar barriers, however the carboxyl species was not observed experimentally either because its C 1s signature could not be resolved (Table S1 lists the calculated peak positions for the C 1s photoelectron for all the fragments) or because it decomposes shortly after being produced via CO formation.…”
Section: Low Temperaturesupporting
confidence: 88%
“…The ultrafine Rh particles in Rh/ED‐KIT‐6 must be active for the hydrogenation of FFR but not as active for FA decomposition to maintain the slow but steady release of active H species in the presence of FA as the hydrogen donor; too high decomposition and low activity for hydrogenation would generate a large quantity of H 2 gas, not the hydrogenation product. In fact, Pd is known as the most active catalyst for FA decomposition to H 2 gas, but as shown in Table , its CHT reaction rate was far below that of Rh/ED‐KIT‐6.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen production from formic acid (FA) is a way to involve renewable biomass sources into the energy cycle [1,2]. The FA decomposition reaction proceeds on mono-, bi-and trimetallic catalysts deposited on oxide or carbon supports [3,4]. Activity and selectivity of the catalysts towards hydrogen production are determined by the nature of their active component, its dispersion, and electronic state of metals.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for platinum deposited on nitrogen-doped carbon nanofibers (N-CNFs) and N-CNTs, it 2 of 13 was shown that the catalytic properties of metal in this reaction are determined by its locally one-type interaction with N Py centers [16]. Among various metals that are active towards FA decomposition, platinum and palladium are the most active catalysts for this reaction [3,17]. It should be noted that the use of N-CNMs as the supports opens new possibilities for enhancing the efficiency of catalysts via the stabilization of highly active and selective atomic metal species [18,19].…”
Section: Introductionmentioning
confidence: 99%